Multistress characterization of fault mechanisms in aerospace electric actuators - Barater, Davide; Immovilli, F.; Soldati, A.; Buticchi, Giampaolo; Franceschini, G.; Gerada, C.; Galea, Michael (IEEE, 2016)
The concept behind the More Electric Aircraft (MEA) is the progressive electrification of on-board actuators and services. It is a way to reduce or eliminate the dependence on hydraulic, mechanical and the bleed air/pneumatic systems and pursue efficiency, reliability and maintainability. This paper presents a specialised test rig whose main objective is to assess insulation lifespan modelling under various stress conditions, especially investigating the interaction between ageing factors. The test set-up is able to reproduce a multitude of environmental and operational conditions at which electric drives and motors, used in aerospace applications, are subjected. It is thus possible to tailor the test cycle in order to mimic the working cycle of an electrical motor during real operation in aircraft application. The developed test-rig is aimed at projecting the technology readiness to higher levels of maturity, in the context of electrical motors and drives for aerospace applications. Its other objective is to validate and support the development of a comprehensive insulation degradation model.